1995
DOI: 10.1210/endo.136.7.7789305
|View full text |Cite
|
Sign up to set email alerts
|

Expression of gonadotropin-releasing hormone (GnRH) receptor gene is altered by GnRH agonist desensitization in a manner similar to that of gonadotropin beta-subunit genes in normal and castrated rat pituitary.

Abstract: It was previously established that the administration of a potent GnRH agonist such as triptorelin (D-Trp6-GnRH) induced desensitization of pituitary gonadotropic cells, resulting in decreased expression of gonadotropin beta-subunit genes and the suppression of LH and FSH synthesis and release. Binding of GnRH to the pituitary is also affected by agonist treatment. To examine the desensitizing effects of GnRH agonist on the expression of the pituitary GnRH receptor (GnRH-R) gene, male rats were given triptorel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
30
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 27 publications
8
30
0
Order By: Relevance
“…It is well known that the elimination of the negative feedback of ovarian steroid hormones on the hypothalamus by ovariectomy causes an increase in the pulsatile LH-RH release from hypothalamic neurons and a marked elevation in the LH-RH concentration in the pituitary portal vessels (36). Accordingly, it was reported that endogenous LH-RH stimulates the synthesis and release of gonadotropins, and increases the number and mRNA expression of its own receptor (35). In keeping with these results, we also found that ovariectomy of rats greatly increased the LH secretion and the LH-RH-R mRNA level in the pituitary.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It is well known that the elimination of the negative feedback of ovarian steroid hormones on the hypothalamus by ovariectomy causes an increase in the pulsatile LH-RH release from hypothalamic neurons and a marked elevation in the LH-RH concentration in the pituitary portal vessels (36). Accordingly, it was reported that endogenous LH-RH stimulates the synthesis and release of gonadotropins, and increases the number and mRNA expression of its own receptor (35). In keeping with these results, we also found that ovariectomy of rats greatly increased the LH secretion and the LH-RH-R mRNA level in the pituitary.…”
Section: Discussionsupporting
confidence: 90%
“…Much evidence indicates that the receptor number is regulated at the pretranslational level by LH-RH-R gene expression (26,35), but data on the posttranscriptional regulation by recycling, modification, or degradation have also been reported (12).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, low frequencies in the range one stimulus every two or four hours appear to preferentially increase FSHβ mRNA levels whereas higher frequencies preferentially stimulate LHβ and α subunit mRNA [13,14]. In vivo, permanent exposure to GnRH leads to a more or less rapid depletion of both FSHβ and LHβ mRNA in a manner that suggests a rapid transcription arrest followed by RNA degradation, while the α-subunit mRNA [15][16][17]. The latter data are consistent with current clinical studies showing that long-term administration of GnRH superagonists induces depletion of LH and FSH but increases free α-subunit levels in the serum of treated patients [18].…”
Section: Gnrh Is Crucial For Regulated Expression Of Gonadotropin Submentioning
confidence: 99%
“…To date, however, much more is known from the first approach. Interestingly, excluding the three gonadotropin subunit genes, GnRH regulates genes essentially associated with the signalling network such as the GnRH receptor itself [17,40], NOS I [41], or PKA and PKC subunit isoforms [42,43] as well as transcription factors such as cFos, cJun or Egr-1. Regulation of the GnRH receptor gene followed a similar extreme dependency on the mode of GnRH stimulation previously revealed for the gonadodotropin β-subunit genes [17,40].…”
Section: The Multigenic Impact Of Gnrh Stimulationmentioning
confidence: 99%
See 1 more Smart Citation